Revisiting the Midwest Invasion Strategy during the Nigerian Civil War - Opeyeoluwa, Rotimi Olajide (Àgídìgbo: ABUAD Journal of the Humanities, 2021)
The Nigerian Civil War was a conflict of great proportion that rocked the foundation of Nigeria between 1967-1970, with attendant horrors and hardships. Extant literatures on this particular incidence have failed to capture the issues in totality and some in recent times have resorted to peddling rumor and historical revisionism depending on the side of the divide they represent. This paper is interested in establishing the motive behind the Biafran Army invasion of the Midwest and how reversal of the initiative led to a chain of unanticipated consequences which collapsed both the initiative as well as the Republic itself in the final analysis. The paper relied on the use of oral historical sources and secondary sources such as books and journals; and is guided by Grand Strategy theory. Premised on the findings, the paper recognizes that the invasion was a necessary strategy and tactics by the Biafran military to open up its intended passage to Lagos in order to seize the Federal capital of Nigeria, but the ensuing operation was bogged down by accusations and counter-accusations of sabotage, mist-steps, reversal in the objective and demoralization of both the Biafran Army and civil populace. The paper concludes that in the face of renewed discussions on the civil war, there is a compelling need to beam the searchlight on intricate aspects of the civil war for informed analysis and knowledge.